Edukasi Herbal Mineral Blok untuk Meningkatkan Efisiensi Pakan Ternak Ruminansia di Desa Gunung Menyan, Bogor - Zylviana, Tengku; Firliani, Syifa Malika; Anbiya, Muhammad Regi; Maharani, Desvita Fitri; Mahenindra, Talenta Parfaibya; Ihsani, Wafi; Safitri, Afizah Dwi; Vebrian, Zaky; Wijaya, Elang Pramudya (Jurnal Pusat Inovasi Masyarakat, 2025)
This community service program was carried out in Gunung Menyan Village, Bogor, with the aim of enhancing farmers’ understanding and skills in producing and utilizing Herbal Mineral Blocks (HMB) as supplementary feed for goats and sheep. The activities were conducted through socialization sessions, tutorial video presentations, and hands-on practice, with effectiveness measured using pre-test and post-test assessments administered to 46 participants. The results indicated a significant increase in knowledge, as evidenced by the paired t-test results (p < 0.05), showing that the participants’ average scores improved. These findings demonstrate that HMB education not only provided new insights but also fostered collective awareness among farmers regarding the importance of healthier and more efficient feed management. From an economic perspective, the use of HMB has the potential to improve livestock quality, increase market value, and strengthen consumer trust in local products. This program serves as an initial step in raising farmers’ awareness of feed quality as a key factor in improving livestock performance.